MANAGEMENT OF UK FINGOLIMOD FIRST DOSE OBSERVATION (FDO). Issue 10 (9th September 2014) - Webber, Bryn; Pugh, Peter; Pull, Emily
Abstract : Background: Fingolimod (Gilenya) is a sphingosine 1-phosphate receptor (S1PR) modulator approved for use in relapsing-remitting multiple sclerosis. Fingolimod can lead to reduced pacemaker cell excitability, slowing heart rate (HR) and, possibly, atrioventricular block. Cardiac monitoring is required for patients starting treatment. Regent's Park Heart Clinics (RPHC) is a cardiology services provider engaged by Novartis Pharmaceuticals UK to provide NHS clinicians with a fingolimod FDO service. Objective: To describe the results of a UK FDO service for fingolimod. Methods: RPHC provided a cardiac physiologist/nurse to visit sites between 0800–1700 hrs with electrocardiography (ECG) equipment. 12-lead ECG was performed at baseline and six hours after initiation with continuous cardiac monitoring throughout. Blood pressure and HR measurement was performed hourly. Where patients had evidence of clinically important cardiac effects, monitoring was extended up to eight hours or overnight. Results: From 4 July 2012 to 19 December 2013, RPHC provided FDO for 419 patients. 397 (95%) were discharged at six hours; 17 (4%) were discharged at eight hours. 3 (0.7%) required an overnight stay. One patient discontinued treatment. Conclusion: Results of an independent FDO service shows fingolimod initiation in 419 patients as largely uneventful with one patient discontinuing therapy. No patients required pharmacological intervention.